Designing A Camouflaged Pavilion in A Bird Park with Metaphor Technique through Section Plan - Lovendianto, Jeremy; Awanda, Ara; Pratama, Aldimas Kurniawan; Fahmi, Rahma Luthfiyya; Muchlis, Nurfahmi (Journal of Architectural Design and Urbanism, 2023)
Metaphor technique adapting organic shape from nature requires advanced technology for its development. Metaphor with regular irregularity concepts provides better camouflage and harmony within context. Irregularity on bird’s nest metaphor is shown better in section plan. Conceptual thinking by section integrating various parameters requires dominant understanding toward structural context. Design context is a pavilion at Nansha Bird Park, Guangzhou, China. The presence of the pavilion should not interfere bird's habitat. Design purpose is making a pavilion that camouflage with minimum interruption toward site. Design approach applies metaphor technique. Metaphor utilizes natural shape (biomimicry) of bird’s nest as nest for humans and birds. By cutting the pavilion into half, the structural complexity of bamboo construction can be shown clearly. Form finding process is done by digital technology and parametric design to achieve optimal form from desired metaphor. Site contextuality is responded specifically by the utilization of bamboo material and construction. Structural system utilizes interwoven bamboo layers to shape monocoque structure with vector-active system. Exploration is done by Rhino 5 and Grasshopper application. Form exploration focuses on bamboo layers as pavilion's structure. Patterns by Grasshopper’s script are applied to each layer. The pavilion’s shape is derived from basic spherical shapes as a metaphor of bird's nest. The resulting shape is stretched to create more space and split in half to expose its structure. Pavilion design responds to site and climate by considering the relationship of function, material, and bamboo construction parameters. Limitation on parametric concepts makes optimization simulation problems have to be adjusted with constructability.